Tổng hợp V2O5 kích thước nanomet bằng phương pháp đốt cháy gel - Đại, Lưu Minh; Nhiệm, Đào Ngọc; Ninh, Vũ Thế; Chức, Phạm Ngọc (Vietnam Journal of Chemistry, 2014)
Vanadium pentoxide powder has been synthesised at low temperature (550oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and vanadium chlorid. The characterization of V2O5 powder is examined by X-ray diffraction (XRD), scanning electron microscopy (SEM) and BET (Brunaure-Emmet-Teller) measurements. Further thermal treatment at 400 - 600oC in 1.5h yields the single phase V2O5 with average size < 50 nm. Its specific surface area is 23.50 m2/g for V2O5.